Between listening and sounding: Exploring the limits of augmented instruments (2022)
This paper explores some of the changed relationships between body and environment that occur when instruments are augmented by electronic or digital circuits. Taking Gregory Bateson’s theorisation of the schizophrenic body (1973) as its starting point, the paper explores situations in which the relationship between the performer, body, and instrument takes on increasingly separate communicational modes, in which the body and its meanings come to resemble the ‘unlabelled metaphor’ of the schizophrenic. A series of instrument/personas are brought before us, representing both the ‘norm’ of acoustic instrumental performances and the extreme limits of instrumental identity, offering critical insight into the space that augmented instruments occupy and transform. In considering some of these changes, and in reaching towards their extremities, attention is paid to the friction or awkwardness that accompanies the metamorphosis. In the same way that the ability of a language to ‘point’ is fraught with inconsistencies and potentials for misunderstanding, so the transformation in instrumental identities does not happen in a smooth and transparent way. However, the changes do create the potential for new sensibilities and forms of critical and ethical awareness.